Visualization of cytosolic ribosomes on the surface of mitochondria by electron cryo‐tomography. (21st August 2017) - Gold, Vicki AM; Chroscicki, Piotr; Bragoszewski, Piotr; Chacinska, Agnieszka
Abstract: We employed electron cryo‐tomography to visualize cytosolic ribosomes on the surface of mitochondria. Translation‐arrested ribosomes reveal the clustered organization of the TOM complex, corroborating earlier reports of localized translation. Ribosomes are shown to interact specifically with the TOM complex, and nascent chain binding is crucial for ribosome recruitment and stabilization. Ribosomes are bound to the membrane in discrete clusters, often in the vicinity of the crista junctions. This interaction highlights how protein synthesis may be coupled with transport. Our work provides unique insights into the spatial organization of cytosolic ribosomes on mitochondria. Synopsis: CryoET and biochemical assays reveal that ribosomes interact specifically with the TOM complex and that nascent chain binding is crucial for ribosome recruitment and stabilization, providing evidence for the coupling of protein synthesis and transport. Cytosolic ribosomes interact specifically with the TOM complex. Nascent chains stabilize ribosomes on the mitochondria surface. Ribosomes are clustered in specific microdomains near the crista. Abstract : CryoET and biochemical assays reveal that ribosomes interact specifically with the TOM complex and that nascent chain binding is crucial for ribosome recruitment and stabilization, providing evidence for the coupling of protein synthesis and transport.